2013
DOI: 10.18705/1607-419x-2013-19-3-242-247
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Elasticity and Endothelium Motovascular Function in Primary Hypothyroidism

Abstract: Objective.To compare aortic elasticity and vasomotor endothelial function in hypertensive and normotensive patients with decompensated primary hypothyroidism (PHT) and after medical compensation. Design and methods. 41 women with PHT were examined, 23 (56 %) subjects had concomitant hypertension. Elasticity of aorta was evaluated by compliance coefficient (CC) and pulse wave velocity (PWV), state of vasomotor endothelial function — by vasodilatation coefficient (VDC). Patients were examined twice: during decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The positive inotropic effect of thyroid hormones is explained not only by their direct effect on the heart (participation in the synthesis and modulation of the activity of contractile proteins and calcium transport), but also by the regulation of systemic vascular resistance. Other literature has shown that with a decrease in thyroid hormones, there is a decrease in aortic elasticity and vascular endothelial dysfunction (Mazur, E.S., Kileinikov, D.V., Semenychev, D.G. et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The positive inotropic effect of thyroid hormones is explained not only by their direct effect on the heart (participation in the synthesis and modulation of the activity of contractile proteins and calcium transport), but also by the regulation of systemic vascular resistance. Other literature has shown that with a decrease in thyroid hormones, there is a decrease in aortic elasticity and vascular endothelial dysfunction (Mazur, E.S., Kileinikov, D.V., Semenychev, D.G. et al, 2013).…”
Section: Discussionmentioning
confidence: 99%